Do bureaucratic organizations lobby? The case of Ghana immigration service - Mohammed, A.K. (The Estonian Journal of Administrative Culture and Digital Governance, 2019)
Information from Seventy interviews and secondary evidence was used to investigate the relationship between Ghana Immigration Service’s (GIS) lobbying and the outcomes it produced. The focus of the investigation was in four areas: the strategies and tactics of lobbying employed; intermediate outcomes achieved; final outcome attained; and the effect of GIS’ lobbying on politics-administration relations. The evidence showed that the strategies succeeded in achieving the desired policy reforms. In addition to this final outcome, GIS’ lobbying also succeeded in attaining intermediate outcomes: increased attention; increased knowledge; and persuasion. Among others, the study’s contributions are that: it has explicated the overlooked conditions under which bureaucratic lobbying or influence is likely to occur; it has shown that lobbying impact should include not only final outcomes but also intermediate effects. Moreover, it has shown that politics-administration relations is a dynamic rather than a static category that is not explained by one best practice model but rather a best fit model or combination of models that is contingent on factors producing transient changes in the relationship
Research Article
Keywords: GIS; Bureaucratic lobbying; Strategies; Tactics; Support and Opposition; Outcomes